2000
DOI: 10.1002/1097-0061(200010)16:14<1273::aid-yea621>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Purification, molecular and kinetic characterization of phosphofructokinase‐1 from the yeast Schizosaccharomyces pombe: evidence for an unusual subunit composition

Abstract: Phosphofructokinase-1 (Pfk-1) from Schizosaccharomyces pombe was purified by 54-fold enrichment to homogeneity elaborating the following steps: (a) Disruption of the cells with glass beads; (b) fractionated precipitation with polyethylene glycol 6000; (c) affinity chromatography on Cibacron-Blue F3G-A-Sephadex G 100; (d) ion exchange chromatography on Resource Q. The native enzyme exhibits a mass of 790+/-30 kDa, as detected by sedimentation equilibrium measurements. The apparent sedimentation coefficient was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…On this basis, a hetero-oligomeric structure of the enzyme is obvious. These results could not be expected, because homo-as well as hetero-oligomeric Pfks have been found in different kinds of yeasts (Heinisch et al, 1989(Heinisch et al, , 1993Schröter and Kopperschläger, 1996;Lorberg et al, 1999;Reuter et al, 2000). From the evolutionary point of view, homo-oligomeric yeast Pfks appear to be more similar to mammalian Pfk in respect of molecular and kinetic properties as described in the literature.…”
Section: Enzyme Structurementioning
confidence: 78%
See 1 more Smart Citation
“…On this basis, a hetero-oligomeric structure of the enzyme is obvious. These results could not be expected, because homo-as well as hetero-oligomeric Pfks have been found in different kinds of yeasts (Heinisch et al, 1989(Heinisch et al, , 1993Schröter and Kopperschläger, 1996;Lorberg et al, 1999;Reuter et al, 2000). From the evolutionary point of view, homo-oligomeric yeast Pfks appear to be more similar to mammalian Pfk in respect of molecular and kinetic properties as described in the literature.…”
Section: Enzyme Structurementioning
confidence: 78%
“…Pfk from the non-fermentative red yeast Rhodotorula glutinis is a homo-tetrameric enzyme, which shares some kinetic properties with mammalian Pfk (Schröter and Kopperschläger, 1996). Studies on Pfk from the fission yeast Schizosaccharomyces pombe revealed a homo-octameric structure of the enzyme (Reuter et al, 2000). Looking at several other yeasts, one gene (PpPFK1 ) was also described for Pfk from Pichia pastoris (PpPfk) encoding the α-subunit.…”
Section: Introductionmentioning
confidence: 99%
“…However, the subunit composition of yeast Pfks varies between species: while the enzymes from S. cerevisiae, K. lactis, P. pastoris and C. albicans are heterooctameric proteins (Kopperschläger et al, 1977;Heinisch et al, 1993;Bär et al, 1997;Lorberg et al, 1999;Kirchberger et al, 2002), those of the fission yeasts Sch. pombe and Y. lipolytica are homo-octameric (Reuter et al, 2000;this work). Thus, the acquisition of an octameric structure does not necessarily result from the interaction between two different types of subunits.…”
Section: Discussionmentioning
confidence: 99%
“…) is about one order of magnitude lower than those known for Pfks from other yeast species, such as S. cerevisiae (Hofmann & Kopperschläger, 1982), Schizosaccharomyces pombe (Reuter et al, 2000), P. pastoris (Kirchberger et al, 2002) and Kluyveromyces lactis (Bär et al, 1997).…”
mentioning
confidence: 81%
“…Recently, we have purified and characterized a particular form of Pfk from Schizosaccharomyces pombe that is composed of only one type of subunit, forming a homo-octameric structure, and was found to be stable in cell-free extract (Reuter et al, 2000).…”
Section: Introductionmentioning
confidence: 99%